2015
DOI: 10.1242/dev.113696
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary proteins Bbs8 and Ift20 promote planar cell polarity in the cochlea

Abstract: Primary cilia have been implicated in the generation of planar cell polarity (PCP). However, variations in the severity of polarity defects in different cilia mutants, coupled with recent demonstrations of non-cilia-related actions of some cilia genes, make it difficult to determine the basis of these polarity defects. To address this issue, we evaluated PCP defects in cochlea from a selection of mice with mutations in cilia-related genes. Results indicated notable PCP defects, including mis-oriented hair cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 62 publications
(85 reference statements)
0
57
0
1
Order By: Relevance
“…These mice show several ciliopathy-related phenotypes including obesity and retinal degeneration (Kulaga et al, 2004; Mykytyn et al, 2004; Tadenev et al, 2011). They also show defective orientation of the sensory hair cells in the inner ear of the cochlea, a common failure found in PCP mutants (May-Simera et al, 2015; Ross et al, 2005). BBS4 null mice show partially penetrant embryonic lethality and all pups which develop to term are runts at birth (Kulaga et al, 2004; Mykytyn et al, 2004).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These mice show several ciliopathy-related phenotypes including obesity and retinal degeneration (Kulaga et al, 2004; Mykytyn et al, 2004; Tadenev et al, 2011). They also show defective orientation of the sensory hair cells in the inner ear of the cochlea, a common failure found in PCP mutants (May-Simera et al, 2015; Ross et al, 2005). BBS4 null mice show partially penetrant embryonic lethality and all pups which develop to term are runts at birth (Kulaga et al, 2004; Mykytyn et al, 2004).…”
Section: Resultsmentioning
confidence: 98%
“…Thus it has been suggested that cilia act independently of, or downstream from, the PCP signalling pathway during cellular polarisation (Wallingford and Mitchell, 2011). However this interpretation is still controversial as a recent report showed a possible upstream function of cilia-related proteins to target a core PCP protein to the specific apical region of the sensory hair cells of the cochlea (May-Simera et al, 2015). In the lens fibres the cilia show distinct polarisation and this prompted us to speculate that cilia have a role in cellular polarisation (Sugiyama et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Eliminating kinocilia mediated apical reorganization results in circular polarized hair cells (Jones et al, 2008). Beyond the kinocilium as a signaling center, the apical acentric polarity development relies on several regulatory factors, such as LGN and Gαi (Tarchini et al, 2016) and Bbs8 and Ift20 (May-Simera et al, 2015) to eliminate microvilli and move the kinocilium into an acentric position and regulate the height and distribution of stereocilia to properly polarize hair cells. The end product of this incompletely understood process (Lu and Sipe, 2016; SchĂŒler et al, 2013) is a highly polarized cell that allows mechanical stimuli to exert changes on the cell’s resting potential depending on the direction of the stimulation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Hair cells show variable stereociliary diameters that clearly are affected by bHLH genes (Jahan et al, 2013, 2015b), but also show the unique stereocilia arrangements of inner and outer hair cells that apparently evolved out of the much simpler stereocilia bundle found in ancestral hair cells of the vestibular type (Lewis et al, 1985). When and how factors that coordinate polarity of hair cells across sensory epithelia (May-Simera et al, 2015) evolved is unclear. Thus, while some connections between Atoh1 level of expression and some of the downstream factors needed for the apical development of the stereocilia bundle are likely (Taura et al, 2016), we do not yet understand how vestibular and cochlear hair cells molecularly evolved their unique stereocilia organization and loss of a kinocilium.…”
Section: Introductionmentioning
confidence: 99%
“…BBS8 was recently shown play a role in establishing planar cell polarity and orientation of cilia in epithelial cells (22). To date, six mutations in the BBS8 gene have been linked to classical BBS (18,23,24).…”
mentioning
confidence: 99%